Epibrassinolide Activates AKT to Trigger Autophagy With Polyamine Metabolism in SW480 and DLD-1 Colon Cancer Cell Lines - Adacan, Kaan; YERLİKAYA, PINAR OBAKAN (The Scientific and Technological Research Council of Turkey, 2020)
Epibrassinolide (EBR), a plant-derived polyhydroxylated derivative of 5 alpha-cholestane, structurally shows similarities to animal steroid hormones. According to the present study, EBR treatment triggered a significant stress response via activating ER stress, autophagy, and apoptosis in cancer cells. EBR could also increase Akt phosphorylation in vitro. While the activation of Akt resulted in cellular metabolic activation in normal cells to proceed with cell survival, a rapid stress response was induced in cancer cells to reduce survival. Therefore, Akt as a mediator of cellular survival and death decision pathways is a crucial target in cancer cells. In this study, we determined that EBR induces stress responses through activating Akt, which reduced the mTOR complex I (mTORC1) activation in SW480 and DLD-1 colon cancer cells. As a consequence, EBR triggered macroautophagy and led to lipidation of LC3 most efficiently in SW480 cells. The cotreatment of spermidine (Spd) with EBR increased lipidation of LC3 synergistically in both cell lines. We also found that EBR promoted polyamine catabolism in SW480 cells. The retention of polyamine biosynthesis was remarkable following EBR treatment. We suggested that EBR-mediated Akt activation might determine the downstream cellular stress responses to induce autophagy related to polyamines.